Peran Zakat Dalam Membina Ekonomi Berkelanjutan: Sebuah Analisis Bibliometrik - Muhammad Agus Futuhul Ma'wa; Ayu Safitri; Fatima Az-Zahra Wairooy; Mindo Mursalina Jen (Jurnal Magister Ekonomi Syariah, 2023)
The problems that hit the global community raise concern. Classical problems such as poverty, hunger, and access to education are other complicated issues that drive leaders to express their commitment to transforming the world through sustainable development goals. Zakat refers to the social responsibility of the Muslim community toward the universal humanitarian mission and the natural environment as a concern of global leaders. The main goal of bibliometric research is to analyze and measure patterns of scientific publications, the distribution of literature, and the development of research. The article data indexed by Scopus and downloaded is the year of publication, the author's name and affiliates, keywords, and geographical distribution. Based on the Scopus database of 23 documents related to the prospects of Zakat in a Sustainable Economy published in the period 2014-2023 and data analyzed using VOSviewer software, The growth trend of the highest Scopus-indexed Sustainable Economy publication reached 5 publications in 2022 and 2023. This research contributes to the literature related to this theme as well as researchers interested in exploring this field. The research results show that there are still very few publications in this field, so researchers are exploring this theme further.